2021
DOI: 10.1093/glycob/cwab113
|View full text |Cite
|
Sign up to set email alerts
|

N-glycans from Paramecium bursaria chlorella virus MA-1D: Re-evaluation of the oligosaccharide common core structure

Abstract: Paramecium bursaria chlorella virus MA-1D is a chlorovirus that infects Chlorella variabilis strain NC64A, a symbiont of the protozoan Paramecium bursaria. MA-1D has a 339-kb genome encoding ca. 366 proteins and 11 tRNAs. Like other chloroviruses, its major capsid protein (MCP) is decorated with N-glycans, whose structures have been solved in this work by using nuclear magnetic (NMR) spectroscopy and MALDI-TOF mass spectrometry along with MS/MS experiments. This analysis identified three N-linked oligosacchari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The purification protocol used for PBCV-1 enabled the identification of the glycan structures of other chloroviruses (Figure ), classified either in the same group of viruses as PBCV-1 or in one of the other three chlorovirus groups (section ). , Of note, the chlorovirus NY-2A was predicted to have two MCPs with a high level of identity between them, and when this method was applied to NY-2A, both glycoproteins were extracted and the N -glycans derived from both proteins were studied together. Collectively, these structural studies established that the chlorovirus MCPs are always N -glycosylated and also revealed other interesting features.…”
Section: Biosynthetic Machinery and The Glycans Produced By Giant Vir...mentioning
confidence: 99%
See 3 more Smart Citations
“…The purification protocol used for PBCV-1 enabled the identification of the glycan structures of other chloroviruses (Figure ), classified either in the same group of viruses as PBCV-1 or in one of the other three chlorovirus groups (section ). , Of note, the chlorovirus NY-2A was predicted to have two MCPs with a high level of identity between them, and when this method was applied to NY-2A, both glycoproteins were extracted and the N -glycans derived from both proteins were studied together. Collectively, these structural studies established that the chlorovirus MCPs are always N -glycosylated and also revealed other interesting features.…”
Section: Biosynthetic Machinery and The Glycans Produced By Giant Vir...mentioning
confidence: 99%
“…Initially, this conserved oligosaccharide core consisted of five monosaccharide units: 179 the four highlighted in Figure 9 together with a so-called distal Xyl residue. However, this view has recently changed after determining the glycan structure of chlorovirus MA-1D, 193 a NC64A virus that produces three different N-glycans, all missing the distal Xyl unit. Accordingly, the conserved core region for all chloroviruses now consists of four sugar units (Figure 9).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Combination of two alkyne-functionalized metabolic reporters, namely ManNAl and SiaNAl, allowed imaging of both sialin-dependent and sialin-independent incorporation pathways. , Cristina De Castro (University of Napoli) described their work on viral glycosylation of giant chloroviruses, on which they identified many original glycans with a new core structure, highly conserved between all chloroviruses. These glycans can be introduced on various peptidic sequences with no typical consensus. Paramecium bursaria Chlorella virus 1 (PBCV-1) encodes several glycosyltransferases, some of which are conserved through other chloroviruses. ,, These glycosyltransferases might become useful tools for chemical glycobiology. Lipopolysaccharide of Alcaligenes faecalis shows promising properties as an adjuvant for vaccines.…”
Section: Daymentioning
confidence: 99%